KEBIJAKAN DINAS PENDIDIKAN KOTA PEKANBARU DALAM MENINGKATKAN KUALITAS PENDIDIK DI SEKOLAH DASAR TAHUN 2015 - Sukma Alfalah; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Policy of Education Office through strategic plan Pekanbaru City in improving quality of quality of educator and education personnel of budget year 2015 is doing program or activity as effort of improving quality of educator and educational staff through formal and non formal education and attempt to rehabilitate damaged buildings or school spaces for improve the quality of education with the construction of school facilities and infrastructure and competent educators. The problem in this research is how is Pekanbaru City Education Office policy in improving the quality of Educator in Primary School year 2015. The purpose of this research is to know the policy of Education Department Pekanbaru City in improving the quality of Educator at elementary school year 2015, and obstacles in its policy. In this research, the researcher uses descriptive research type with qualitative method approach. This research is located in Pekanbaru City Education Office. To get information needed in this research, research using purposive sampling technique. Data collection techniques used were interview, observation and documentation. For data analysis is done by descriptive method obtained from observation directly on the object of research and indept interview by connecting qualitatively.The results of this study can be concluded that the policy of Education Department Pekanbaru City in improving the quality of Educators in Primary Schools in 2015, has not run well on the aspect of the attitude of implementers in which the lack or not realization of the executor attitude expected in improving the quality of educators, are at managerial level, while at the executive level still lack awareness. Obstacles in the policy of the Education Office in improving the quality of educators in elementary schools in Pekanbaru City, namely (a) lack of teachers in the field of technology and communication, (b) teacher motivation is still low to improve Human Resources, (c) inaccurate data in complete certification files, and (d) lack of budget allocations for teacher development and development.Keywords: Policy, Quality of Educator, Elementary School